Integrated Engineering Project Management Approach for Typical Small to Medium Manufacturing Companies - Erry Yulian Triblas Adesta; Mohammed Abdullah K B; Yahya A Alazemi (Institute of Advanced Engineering and Science, 2017)
The aim of this paper is to identify the problem extents and successfully applying project management in SMEs with a focus on manufacturing industries. The organization of the study was mainly divided into the activity of literature study and the investigation through a survey conduct aimed to measure the awareness and implementation of project management at the selected SMEs in Malaysia. The questionnaire was designed with a section (Section A) involving project management in general and another section (Section B) involving the implementation of it. It was found that the level of awareness and implementation of project management especially in the selected small and medium manufacturing companies in Malaysia was quite satisfying. Most of the manufacturing companies were implementing project management, but the level was depending on the organization in the company itself.